Vitamin D supplementation practice in general paediatric clinics is suboptimal—a survey of current practice in an inner city London hospital. (29th September 2015) - Joshi, A; Gore, C; Coren, M
Abstract : Aims: Vitamin D supplementation is recommended for all children under the age of 5 years in the UK. Due to its ethnic diversity the population of inner-city London is at increased risk for vitamin D deficiency. The authors aimed to identify current practice of vitamin D supplementation in a paediatric outpatient setting and to identify if particular risk groups exist. Methods: Cross-sectional questionnaire survey of families attending a variety of paediatric outpatient appointments in July and August 2009. Comparison of practice against gold standard set by Scientific Advisory Committee on Nutrition 2007. Statistical tests used: χ 2 . Results: N=100 families participated. Children's median age was 5.0 years (IQR 2.0–10.0 years). 45/100 (45%) attended for conditions potentially increasing risk of nutritional deficiencies: 31/45 were seen to "monitor growth", gastroenterology or allergic problems; 14/45 for renal or haematological conditions. Ethnicity was varied: 35% White, 28% Afro-Caribbean, 20% Asian/Middle East, 6% mixed race, 11% other. White and Afro-Caribbean children were significantly less likely to be on vitamin supplements compared to children from Asian/Middle Eastern and "other" ethnic background (p=0.047). 19/100 (19%) were described as having food allergies, but foods, such nuts, egg or milk were avoided in 37/100 (37%). 22/100 (22%) of all children were taking vitamin supplements. Of the 44 children age <5 years only 6 (13.6%) were taking vitamin supplements. 6/44 children <5 years were avoiding milk, only 1/6 was taking supplements. Conclusion: Only 13.6% of children age <5 years were receiving vitamin supplements; therefore, government recommendations were not met. Supplementation varied between ethnic groups, supplementation was best in those from Asian/Middle Eastern background, possibly reflecting the efforts made to increase uptake of supplementation in those communities. The surveyed group of patients is selected and at higher risk of deficiencies and nevertheless supplementation is poor. Targeted education of families and healthcare professionals to promote increased uptake/recommendation of vitamin D supplementation may be required.